Copb2 is essential for embryogenesis and hypomorphic mutations cause human microcephaly. (19th September 2017) - DiStasio, Andrew; Driver, Ashley; Sund, Kristen; Donlin, Milene; Muraleedharan, Ranjith M; Pooya, Shabnam; Kline-Fath, Beth; Kaufman, Kenneth M; Prows, Cynthia A; Schorry, Elizabeth; Dasgupta, Biplab; Stottmann, Rolf W
Abstract: Primary microcephaly is a congenital brain malformation characterized by a head circumference less than three standard deviations below the mean for age and sex and results in moderate to severe mental deficiencies and decreased lifespan. We recently studied two children with primary microcephaly in an otherwise unaffected family. Exome sequencing identified an autosomal recessive mutation leading to an amino acid substitution in a WD40 domain of the highly conserved Coatomer Protein Complex, Subunit Beta 2 (COPB2) . To study the role of Copb2 in neural development, we utilized genome-editing technology to generate an allelic series in the mouse. Two independent null alleles revealed that Copb2 is essential for early stages of embryogenesis. Mice homozygous for the patient variant ( Copb2 R254C/R254C ) appear to have a grossly normal phenotype, likely due to differences in corticogenesis between the two species. Strikingly, mice heterozygous for the patient mutation and a null allele ( Copb2 R254C/Zfn ) show a severe perinatal phenotype including low neonatal weight, significantly increased apoptosis in the brain, and death within the first week of life. Immunostaining of the Copb2 R254C/Zfn brain revealed a reduction in layer V (CTIP2 + ) neurons, while the overall cell density of the cortex is unchanged. Moreover, neurospheres derived from animals with Copb2 variants grew less than control. These results identify a general requirement for COPB2 in embryogenesis and a specific role in corticogenesis. We further demonstrate the utility of CRISPR-Cas9 generated mouse models in the study of potential pathogenicity of variants of potential clinical interest.